2000
DOI: 10.1097/00007435-200003000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Trends of Sexually Transmitted Diseases in China

Abstract: The incidence of STDs has continued to increase in China from 1989 to 1998. The epidemic patterns are different from rates in developed counties in which behavior interventions have been successfully implemented, suggesting the need for active behavioral-intervention programs in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
103
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(110 citation statements)
references
References 11 publications
6
103
1
Order By: Relevance
“…In addition, more than half of all STIs in China occur among those aged 29 or younger. 20 Sex education programs have been offered in schools since 1985, but these have generally not addressed the reduction of high-risk behaviors among youth. 6,21 Indeed, the curriculum focuses on basic facts about reproduction, and discussion of contraception tends to be excluded out of concern that it could be seen as promoting sexual activity among youth.…”
mentioning
confidence: 99%
“…In addition, more than half of all STIs in China occur among those aged 29 or younger. 20 Sex education programs have been offered in schools since 1985, but these have generally not addressed the reduction of high-risk behaviors among youth. 6,21 Indeed, the curriculum focuses on basic facts about reproduction, and discussion of contraception tends to be excluded out of concern that it could be seen as promoting sexual activity among youth.…”
mentioning
confidence: 99%
“…12 STI has become the third most common infectious disease in China. 13 According to the National STD Surveillance System, close to 1 million new STI cases have been reported annually in recent years, and there was an average annual increase of 39% from 1985 to 2004.…”
mentioning
confidence: 99%
“…17 The National STD Surveillance System indicated that the majority of STIs were acquired through extramarital sex, including commercial sex. 12 Existing studies on FSWs have relied largely on selfreported STI. Of limited studies that reported biologically confirmed STI, the prevalence ranged from 30% to 85%.…”
mentioning
confidence: 99%
“…1 After three decades of economic reform, however, the prevalence of STIs in China increased dramatically. 2 Although STIs can cause significant morbidity, treatments for STIs in China often were inadequate.…”
mentioning
confidence: 99%
“…11 The dissolution of social health insurance in China through the 1990s significantly increased the out-ofpocket costs for patients, 12 and, therefore, low income could be a barrier to access to healthcare for Chinese women with STIs. Unlike in western countries, sex education was very 1 Old Dominion University, Norfolk, Virginia. 2 The University of Chicago, Chicago, Illinois.…”
mentioning
confidence: 99%